The elucidation of novel capsular genotypes of Haemophilus influenzae type b with the polymerase chain reaction. - Leaves, N; Falla, T; Crook, D (1995)
Molecular characterization is an important pre-requisite for post-vaccine studies of Haemophilus influenzae type b (Hib). Three capsular genotyping patterns, b(S), b(G) and b(V), have been described in the major phylogenetic lineage of Hib. However, in a recent series of prospective studies, three new hybridisation patterns were observed among 425 strains of Hib. Four pairs of polymerase chain reaction (PCR) primers were used to identify the capsular gene (cap) structure of these Hib strains. This showed that the strains possessed simple DNA re-arrangements. In two instances a change in restriction enzyme recognition site was the most likely cause of the new hybridisation pattern. The third strain possessed a cap b locus consisting of intact tandem repeats of cap b in a b(S) background. It was reasoned that a similar cap b locus would not be readily recognised by hybridisation in a b(G) background, and b(G) strains were therefore characterized by the PCR method. This showed one of 35 b(G) strains to possess a cap locus with intact tandem repeat copies of cap b. The novel capsular genotypes described here are rare, but can be detected rapidly and accurately by a combination of PCR and capsular genotyping hybridisation patterns.